Takotsubo Cardiomyopathy Caused By Acute Ischemic Stroke. - Tahir, Hassan; Hussain, Khandakar; Ullah, Saad (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Takotsubo cardiomyopathy, also known as stress cardiomyopathy, usually occurs secondary to extreme physical and emotional stress. Subarachnoid hemorrhage has been strongly related to stress cardiomyopathy due to catecholamine surge in such patients; however, ischemic stroke has been rarely associated with takotsubo cardiomyopathy. Whether ischemic stroke is the cause or the result of takotsubo cardiomyopathy is difficult to ascertain in some cases. We present a case of a 78-year-old female who came with stroke symptoms and developed cardiogenic shock secondary to takotsubo cardiomyopathy.